Simulation of Updraft and Downdraft Gasification Using Computational Fluid Dynamics (CFD) for Production of Syngas from Chicken Manure Waste - Utami, Amaliyah Rohsari Indah; Anindya Nabila Salma; Daffa Rayhan Betha Muchtar; Neni Sintawardani; Suwandi (Universitas Telkom, 2026)
The rapid industrialization of the poultry sector has led to significant environmental challenges, including nutrient pollution, odor, and greenhouse gas emissions from improper manure management. This study explores the potential of chicken manure waste gasification as a sustainable solution for renewable energy production while addressing waste disposal issues. Utilizing Computational Fluid Dynamics (CFD) simulations in ANSYS Fluent software, the research investigates updraft and downdraft gasification processes under varying operational conditions, including air flow velocity and temperature. The simulation model demonstrated high accuracy in predicting syngas composition, with average errors of 0.1657% at 580°C and 0.0969% at 680°C, validating its reliability. The optimal dimensions for updraft (30 cm diameter, 40 cm height) and downdraft (16.5 cm diameter, 60 cm height) gasifiers were determined to align with industry standards. Results revealed that air flow velocity significantly influenced syngas composition; moderate increases enhanced CO production in updraft configurations, while excessive airflow in downdraft setups reduced CO concentration due to over-oxidation. Temperature optimization further improved syngas quality, with higher temperatures (800°C) increasing CO and H₂ concentrations. The H₂/CO ratio remained stable under updraft conditions but exhibited more significant variability in downdraft setups due to differences in reaction kinetics and flow dynamics. These findings highlight the importance of precise control over operational parameters to optimize syngas yield and composition for energy applications. Future work should focus on refining simulation models, exploring diverse feedstocks, and enhancing process efficiency to advance sustainable waste-to-energy technologies.